FDI in Mexico: An empirical assessment of employment effects - Peter Nunnenkamp; José Eduardo Alatorre Bremont (Kiel Institute for the World Economy (IfW), 2007)
We raise the question whether foreign direct investment (FDI) has contributed to employment generation in Mexico and, thereby, helped overcome the country's pressing labor market problems. The analysis draws on highly disaggregated FDI and employment data covering almost 200 manufacturing industries. We estimate dynamic labor demand functions for blue and white collar workers, including both FDI and its interaction with major industry characteristics. By employing the GMM estimator suggested by Arellano and Bond, we account for the relatively short time dimension of our panel (1994-2006). It turns out that FDI has a significantly positive, though quantitatively modest impact on manufacturing employment in Mexico. Moreover, we find no evidence supporting the widely held view that FDI adds to white collar employment in the first place. However, the positive effect on blue collar employment diminishes with increasing skill intensity of manufacturing industries.
Keywords: F23; J23; 330; Employment; Blue and white collar workers; Manufacturing sector; Mexico; Foreign direct investment; Direktinvestition; Industrielle Beschäftigung; Beschäftigungseffekt; Qualifikation; Schätzung; Mexiko